2017
DOI: 10.1007/s13187-017-1212-9
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Cessation Counseling: Attitudes and Practices among Yemeni Dental Professionals

Abstract: Tobacco use is a significant health problem in Yemen and worldwide. Dental practitioners can play a pivotal role in educating their patients on the risk of smoking and motivating them to quit. This study aimed to assess the attitudes towards and practices of tobacco cessation counseling (TCC) among Yemeni dental professionals and to evaluate whether such attitudes and practices are associated with gender, smoking status, and years since graduation. In this cross-sectional study, a self-administered questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
31
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 30 publications
7
31
4
Order By: Relevance
“…who are current tobacco and/ or areca nut users. This is completely different from most of the studies reported where a signi cant percentage of dental surgeons use tobacco, specially smoking [25].…”
contrasting
confidence: 77%
See 3 more Smart Citations
“…who are current tobacco and/ or areca nut users. This is completely different from most of the studies reported where a signi cant percentage of dental surgeons use tobacco, specially smoking [25].…”
contrasting
confidence: 77%
“…We have observed that only 42.7% of the respondents had the habit of inquiring regarding tobacco usage from all of their patients routinely. This is much less than the reported numbers in the literature [25]. Giving up the SLT habit early will de nitely bene t the patient as the chances of developing adverse effects increase with the duration of SLT use.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Smokers constituted 27% of the study sample. Recent studies reported almost the same prevalence of smoking among a sample of physicians and dentists in Iraq and Saudi Arabia 14,15 , but higher than dentists in Yemen where 20% of the study sample were smokers 16 . In the current study, a smoking dentist was more likely to be: male, age less than 40 years, and a professional experience of less than 15 years.…”
Section: Discussionmentioning
confidence: 65%